Phenotypic Spectrum of Seizure Disorders in MBD5-Associated Neurodevelopmental Disorder. (April 2021) - Myers, Kenneth A.; Marini, Carla; Carvill, Gemma L.; McTague, Amy; Panetta, Julie; Stutterd, Chloe; Stanley, Thorsten; Marin, Samantha; Nguyen, John; Barba, Carmen; Rosati, Anna; Scott, Richard H.; et al.
Abstract : Objective: To describe the phenotypic spectrum in patients with MBD5-associated neurodevelopmental disorder (MAND) and seizures; features of MAND include intellectual disability, epilepsy, psychiatric features of aggression and hyperactivity, and dysmorphic features including short stature and microcephaly, sleep disturbance, and ataxia. Methods: We performed phenotyping on patients with MBD5 deletions, duplications, or point mutations and a history of seizures. Results: Twenty-three patients with MAND and seizures were included. Median seizure onset age was 2.9 years (range 3 days–13 years). The most common seizure type was generalized tonic-clonic; focal, atypical absence, tonic, drop attacks, and myoclonic seizures occurred frequently. Seven children had convulsive status epilepticus and 3 nonconvulsive status epilepticus. Fever, viral illnesses, and hot weather provoked seizures. EEG studies in 17/21 patients were abnormal, typically showing slow generalized spike-wave and background slowing. Nine had drug-resistant epilepsy, although 3 eventually became seizure-free. All but one had moderate-to-severe developmental impairment. Epilepsy syndromes included Lennox-Gastaut syndrome, myoclonic-atonic epilepsy, and infantile spasms syndrome. Behavioral problems in 20/23 included aggression, self-injurious behavior, and sleep disturbance. Conclusions: MBD5 disruption may be associated with severe early childhood-onset developmental and epileptic encephalopathy. Because neuropsychiatric dysfunction is common and severe, it should be an important focus of clinical management.